275 Phenotypic relationships between heart score and feed efficiency, carcass, and pulmonary arterial pressure traits. (30th November 2020) - Heffernan, Kathryn R; Speidel, Scott; Thomas, Milt; Enns, Mark; Holt, Tim
Abstract: Pulmonary hypertension (PH) can lead to premature mortality in fed cattle and is often called Feedlot Heart Disease (FHD). To date, pulmonary arterial pressure (PAP) has been the only indicator trait of PH that has been evaluated. The objective of this study was to evaluate relationships between heart score (using heart score as a phenotype for PH) and PAP, carcass, and feed efficiency traits in fattening Angus steers. Our hypothesis was that feed efficiency and carcass traits, along with PAP, would demonstrate a strong relationship with heart score. Feed efficiency, carcass, PAP and heart score data from 89 Black Angus steers from Colorado State University Beef Improvement Center were collected and used for this study. Evaluations were performed using a multiple linear regression model, which included heart score as a categorical fixed effect and age as a continuous fixed effect. Least Square Means, pairwise comparisons, and ANOVA tables were constructed per trait. PAP (P < 0.001) showed an important relationship to heart score and average dry matter (P < 0.10) intake approached importance to heart score. In general, feed efficiency and carcass traits decreased as heart score increased, but PAP was the only trait with a strong relationship to heart score (P < 0.05). This led us to reject our hypothesis.